How cost-effective is it to leave perineal skin unsutured? - Petrou, S; Gordon, B; Mackrodt, C; Fern, E; Ayers, S; Grant, A; Truesdale, A; McCandlish, R (Mark Allen Healthcare, 2001)
This paper describes a cost-effectiveness evaluation based on a randomized controlled trial comparing two policies for surgical repair of perineal trauma. Data were collected for 1780 women who were randomly allocated to either a two-stage postpartum perineal repair policy leaving the skin unsutured (n=890) or a three-stage postpartum perineal repair policy that required suturing of the skin (n=890). The two-stage postpartum perineal repair policy was found to reduce the risk of adverse outcomes at 10days and at 3months, without leading to a significant increase in health-care costs. A widespread adoption of a two-stage postpartum perineal repair policy leaving the skin unsutured following perineal trauma is likely to represent a cost-effective use of health-care resources.